2020
DOI: 10.3389/fimmu.2019.03083
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme A in Chikungunya and Other Arboviral Infections

Abstract: Granzyme A (GzmA) is secreted by cytotoxic lymphocytes and has traditionally been viewed as a mediator of cell death. However, a growing body of data suggests the physiological role of GzmA is promotion of inflammation. Here, we show that GzmA is significantly elevated in the sera of chikungunya virus (CHIKV) patients and that GzmA levels correlated with viral loads and disease scores in these patients. Serum GzmA levels were also elevated in CHIKV mouse models, with NK cells the likely source. Infection of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 114 publications
(167 reference statements)
7
53
1
Order By: Relevance
“…This result contradicts previous findings that showed that human inactive GzmA was not able to induce the production of inflammatory cytokines in human monocytes (17). In addition, it has been shown that the inflammatory activity of mouse GzmA in vivo is significantly affected when GzmA inactivated with an inhibitor is used (48). The reasons for this discrepancy are not clear yet and will require further investigation.…”
Section: Regulation Of Inflammatory Cytokine Network and Cytokine Stormcontrasting
confidence: 86%
See 1 more Smart Citation
“…This result contradicts previous findings that showed that human inactive GzmA was not able to induce the production of inflammatory cytokines in human monocytes (17). In addition, it has been shown that the inflammatory activity of mouse GzmA in vivo is significantly affected when GzmA inactivated with an inhibitor is used (48). The reasons for this discrepancy are not clear yet and will require further investigation.…”
Section: Regulation Of Inflammatory Cytokine Network and Cytokine Stormcontrasting
confidence: 86%
“…Thus, it is not clear yet if PAR2 is activated by GzmA and the role of PAR2 in GzmAmediated cytokine induction. A recent study found that a PAR-2 inhibitor (I-343) inhibited foot swelling induced by in vivo administration of GzmA (48). This result suggests that PAR-2 could be directly or indirectly involved in some of the biological functions of GzmA, but its specific role in the regulation of GzmA-mediated inflammatory cytokine production will require further experimental validation.…”
Section: Endothelial Barrier Permeability: Any Role For Protease Actimentioning
confidence: 99%
“…In addition, in our system, active or inactive GzmA did not potentiate the effect of LPS. Other studies employing inhibitors or enzymatically inactive mutants have also found that enzyme activity is required for the inflammatory action of mouse and human GzmA 16 , 50 . While the reasons for these apparently contradictory results are not known, it cannot be ruled out that both active and inactive forms of GzmA act as proinflammatory mediators in the plasma of septic patients.…”
Section: Discussionmentioning
confidence: 97%
“…Limitations include the inconsistent penetrance of overt liver lesions, as well as no elevation in bilirubin levels and high variability in elevated serum AST levels (although the latter does recapitulate the variability seen in human YFV infections). As illustrated herein, the model can be used to assess vaccine efficacy, but it may also find utility for other studies involving, for instance, fetal infection/development [ 48 , 49 ], immunopathology [ 50 ] and/or tropism [ 51 ].…”
Section: Discussionmentioning
confidence: 99%